2021
DOI: 10.1038/s41598-021-02215-0
|View full text |Cite
|
Sign up to set email alerts
|

Multifragmentary patellar fracture has a distinct fracture pattern which makes coronal split, inferior pole, or satellite fragments

Abstract: The present study aimed to map the location and frequency of fracture lines on the coronal articular and sagittal planes in multifragmentary patellar fractures. 66 multifragmentary patellar fractures were digitally reconstructed using the 3D CT mapping technique. The coronal articular surface and midsagittal fracture maps were produced by superimposing each case over a single template. Each fracture line was classified based on the initial displacement and orientation. We evaluated the frequency and direction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Inferior pole fractures of the patella commonly present comminution at the distal fragments, occurring in 88% of cases in a recent series report. 2 Cho et al 4 observed interesting results of fracture comminution patterns using a three-dimensional (3D) computed tomography mapping technique, in which they often observed that horizontal fracture lines at distal the 1/3 of the articular surface and inferior pole and vertical fracture lines creating satellite fragments on the periphery of the bilateral facet. 4 Furthermore, coronal splitting fracture lines were also occasionally observed in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Inferior pole fractures of the patella commonly present comminution at the distal fragments, occurring in 88% of cases in a recent series report. 2 Cho et al 4 observed interesting results of fracture comminution patterns using a three-dimensional (3D) computed tomography mapping technique, in which they often observed that horizontal fracture lines at distal the 1/3 of the articular surface and inferior pole and vertical fracture lines creating satellite fragments on the periphery of the bilateral facet. 4 Furthermore, coronal splitting fracture lines were also occasionally observed in the sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…2 Cho et al 4 observed interesting results of fracture comminution patterns using a three-dimensional (3D) computed tomography mapping technique, in which they often observed that horizontal fracture lines at distal the 1/3 of the articular surface and inferior pole and vertical fracture lines creating satellite fragments on the periphery of the bilateral facet. 4 Furthermore, coronal splitting fracture lines were also occasionally observed in the sagittal plane. 4 Owing to these multifragmentary fracture patterns and inherent weak small bone in distal fragments, the tension band wiring technique is not feasible because it requires an intact cortical buttress to withstand compression and firm fixation to withstand the tensile forces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations